A randomized controlled clinical study of acupuncture therapy for Seborrheic alopecia in young and middle ages: Study protocol clinical trial (SPIRIT compliant). Issue 17 (April 2020) - Chen, Qiulian; Tao, Yun; Wang, Longjun; Zhang, Jinfang; Sun, Bichen; Yang, Xiaoli
Abstract: Introduction: Seborrheic alopecia (SA) has clinical manifestations, duration of disease, and priorities. In the current situation where there are many and complicated clinical treatments, Western medicine treatment can delay and control the development of the disease and promote hair regeneration. However, some patients may aggravate symptoms after taking the drug, and the condition is easy to repeat after stopping the drug. Acupuncture is an important method for non-surgical treatment of SA, and it has various methods, low side effects, high safety, and simple and economical. Therefore, we will use a clinical randomized controlled study to explore the effect of acupuncture on SA, and provide a new idea and reference for the treatment of this disease. Methods/design: We will select 60 patients diagnosed with SA. They will be randomly divided into intervention group and control groups. The control group will be given conventional treatment measures. The intervention group will receive acupuncture. Efficacy will be evaluated by comparing the skin lesion score and dermatological quality of life index before and after treatment. Discussion: This trial may provide evidence regarding the clinical effectiveness, safety, and cost-effectiveness of acupuncture for patients with SA. Trial registration number: CTR2000030430